Aqueous zinc ion battery electrolyte and preparation method and application thereof
By adding specific organic additives, such as folic acid, to the electrolyte of aqueous zinc ion battery, the dendrite and corrosion problems in zinc ion battery during zinc negative electrode plating/peeling are solved, and the cycle stability and capacity retention rate of the battery are improved.
Patent Information
- Application Number
- CN202411761117.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
AI Technical Summary
The existing aqueous zinc ion batteries have problems such as zinc dendrites, dead zinc and side reactions during the zinc negative electrode plating/stripping process, resulting in an increase in the battery capacity attenuation rate and poor circulation stability.
An electrolyte containing soluble zinc salts and specific organic additives, such as folic acid, malic acid or chloramphenicol, is prepared by mixing evenly through ultrasonic to prevent the formation of zinc dendrites.
Effectively prevent the growth and corrosion reaction of zinc dendrites, improve the reversibility and stability of the zinc anode/electrolyte interface, extend the cycle life of aqueous zinc ion batteries, and reduce costs.
Smart Images

Figure CN119725795A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion battery electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have become the most widely studied rechargeable batteries due to their high energy density, good cycle stability, rechargeability, and mature commercialization. They are used in large-scale energy storage equipment, new energy vehicles, portable electronic products, and other fields. However, lithium-ion batteries still have fatal disadvantages, such as scarce lithium resources, high prices, cumbersome and complex assembly processes, and safety issues caused by the use of organic electrolytes. Therefore, compared with traditional organic energy storage systems, low-cost, high-safety aqueous metal-ion batteries are expected to replace traditional lithium-ion batteries.
[0003] Metallic zinc has a high energy density (5855Ah L -1 、820Ah kg -1 ), low cost, high safety and easy assembly. In addition, metallic zinc has the advantages of extremely high redox potential (-0.76V vs. SHE, standard hydrogen electrode) and inertness to H2O and O2, making it an ideal negative electrode material for aqueous zinc-ion batteries. However, there are also many problems in the zinc negative electrode electroplating / stripping process, including zinc dendrites, dead zinc, side reactions (corrosion, hydrogen evolution, passivation), etc., which lead to an increase in the battery capacity decay rate, resulting in low coulomb efficiency and poor long-cycle stability during the reversible cycle. Among them, inhibiting the growth of dendrites is one of the important ways to improve the electrochemical performance of zinc-ion batteries. During the deposition process, zinc ions tend to nucleate at lower energy positions to form some tiny zinc dendrites, and then the charges will gather here to form a strong electric field. Due to electrostatic effects, zinc ions will be attracted to the tip to nucleate and grow, resulting in a "tip effect". The continuous growth of zinc dendrites leads to battery capacity decay, and even pierces the diaphragm, eventually causing battery failure.
[0004] Based on the above situation, it is necessary to study the technology that can inhibit the formation of zinc dendrites in zinc-ion batteries. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide an aqueous zinc ion battery electrolyte and a preparation method and application thereof, wherein the aqueous zinc ion battery electrolyte can inhibit the formation of dendrites at the negative electrode of the zinc ion battery, thereby improving the cycle stability of the battery.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] An aqueous zinc ion battery electrolyte contains a soluble zinc salt and an organic additive, wherein the concentration of the soluble zinc salt in the electrolyte is 1 to 3 mol / L; and the concentration of the organic additive in the electrolyte is 0.25 to 3 g / L.
[0008] The organic additive is one or more of folic acid, malic acid and chloramphenicol.
[0009] The soluble zinc salt is one or more of zinc borate, zinc chloride, zinc trifluoromethanesulfonate, zinc sulfate, zinc perchlorate and zinc acetate.
[0010] A method for preparing an aqueous zinc ion battery electrolyte comprises adding an organic additive into a solution containing a zinc salt and uniformly mixing the solution by ultrasonic mixing.
[0011] An application of an aqueous zinc ion battery electrolyte, wherein the aqueous zinc ion battery electrolyte is used in an aqueous zinc ion battery, wherein the aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm, and an electrolyte; the negative electrode is one of zinc sheet, zinc foil, zinc plate, and zinc powder material;
[0012] The positive electrode is at least one of zinc metal, Prussian blue analogs, manganese-based oxides, vanadium-based oxides, and organic materials;
[0013] The diaphragm is one of glass fiber, single-layer polypropylene film, single-layer polyethylene film, polypropylene + ceramic coating film, polyethylene + ceramic coating film, double-layer polypropylene / polyethylene film, double-layer polypropylene polypropylene and three-layer polypropylene / polyethylene / polypropylene film, Nafion membrane, PVDF membrane, polyester membrane, cellulose membrane, polyimide membrane, non-woven fabric diaphragm, and inorganic composite membrane.
[0014] The Prussian blue analogue is one of HCF, ZnHCF and CuHCF.
[0015] The manganese-based oxide is one of MnO2, Mn2O3, Mn3O4, ZnMn2O4, and MgMn2O4.
[0016] The vanadium-based oxides are V2O5, VO2, V2O3, V6O 13 , one of vanadates NaV3O8·1.5H2O, LiV3O8, and CuV2O6.
[0017] The organic material is polyaniline or quinone compound.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The organic additive of the present invention selects folic acid, malic acid or chloramphenicol molecules to be adsorbed on the surface of zinc foil, so that the ion flux is uniform, and uniform zinc deposition and peeling are obtained. Water molecules can be effectively prevented from directly contacting the anode surface, and the growth of side reactions and zinc negative electrode dendrites can be suppressed. In addition, folic acid, malic acid or chloramphenicol molecules can replace active water molecules or sulfate anions in the original solvation layer of zinc ions, so that the solvation structure of zinc ions is weakened, and the reversibility and stability of the zinc anode / electrolyte interface are improved. Therefore, the organic additive can suppress side reactions such as dendrites and corrosion, which helps to extend the cycle life of aqueous zinc ion batteries. In addition, folic acid, malic acid or chloramphenicol are low in cost, which is of great significance for building high-performance and low-cost aqueous zinc ion batteries.
[0020] The symmetrical battery prepared with the electrolyte of the present invention has a cycle stability of up to 8300 hours, the asymmetric battery has a coulombic efficiency (936 cycles, 99.37%), and the MnO2||Zn long cycle performance (900 cycles, 99.94%, capacity retention rate 77.1%). BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Zn||Zn symmetric cell of Example 1 is at a current density of 1 mA cm -2 , the deposition capacity is 1 mAh cm -2 SEM image after 30 cycles under the test conditions.
[0022] Figure 2 It is the linear scan curve (LSV) diagram of Example 1 and Comparative Example 1.
[0023] Figure 3 The Zn||Zn symmetric battery prepared in Example 1 and Comparative Example 1 was subjected to a current density of 0.2 mA cm -2 , the deposition capacity is 0.2 mAh cm -2 Comparison of cycle performance under test conditions.
[0024] Figure 4 The Zn||Zn symmetric cells prepared in Examples 1 to 6 and Comparative Example 1 were subjected to a current density of 2 mA cm -2 , the deposition capacity is 2 mAh cm -2 Comparison of cycle performance under test conditions.
[0025] Figure 5 The Zn||Zn symmetric cell of Comparative Example 1 is -2 , the deposition capacity is 1 mAh cm -2 SEM image after 30 cycles under the test conditions.
[0026] Figure 6The Cu||Zn asymmetric cells prepared in Examples 7, 11, 12, 13 and Comparative Example 2 were subjected to a current density of 1 mA cm -2 , the deposition capacity is 1 mAh cm -2 Comparison of cycle performance under test conditions.
[0027] Figure 7 The Cu||Zn asymmetric cells prepared in Examples 7 to 10 were tested at a current density of 8 mA cm -2 , the deposition capacity is 4 mAh cm -2 Comparison of cycle performance under test conditions.
[0028] Figure 8 This is a comparison chart of the cycle performance of the full batteries prepared in Example 13 and Comparative Example 3 under 5C test conditions. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] An aqueous zinc ion battery electrolyte and a preparation method thereof, comprising the following steps:
[0032] 1) Weigh 5.75 g zinc sulfate and mix with 10 mL deionized water and stir evenly to obtain 2 mol L -1 Zinc sulfate solution;
[0033] 2) Weigh 1 mg of folic acid additive and mix with the obtained 2 mol L -1 The zinc sulfate solution was ultrasonically mixed for 2 h and then stirred at a speed of 600 r / min for 6 h to prepare the electrolyte used.
[0034] Application of aqueous zinc ion battery electrolyte:
[0035] With zinc foil (50 μm) as positive and negative electrodes and glass fiber as separator, 130 μL of the above electrolyte was added to assemble a Zn||Zn symmetric battery, and the linear sweep curve (LSV) was tested. Its cycle performance was also tested at 20°C. Figure 1 It can be seen that the surface of the zinc electrode in Example 1 is flat and uniform, and no obvious dendrites are generated, indicating that the addition of folic acid electrolyte can effectively inhibit zinc dendrites. The aqueous zinc ion electrolyte prepared in Example 1 was used to assemble a Zn||Zn symmetrical battery, and a charge and discharge test was performed on a blue electric test system. Figure 2 As shown, the corrosion potential of the LSV curve of Example 1 is more positive and the corrosion current is smaller, indicating that the aqueous zinc ion battery electrolyte prepared in Example 1 improves the corrosion resistance of the zinc negative electrode. Figure 3As shown, at a current density of 0.2 mA cm -2 , the deposition capacity is 0.2 mAh cm -2 Under the test conditions, compared with the battery cycle life without additives, the battery cycle life is as high as 8300h after adding folic acid additives. Figure 4 As shown, at a current density of 2 mA cm -2 , the deposition capacity is 2 mAh cm -2 Under the test conditions, the cycle life of the Zn||Zn symmetric battery can exceed 900h.
[0036] Comparative Example 1
[0037] Prepare 2M ZnSO4 electrolyte in additive-free system: weigh 5.75g zinc sulfate and mix with 10mL deionized water and stir well to obtain 2mol L -1 Zinc sulfate solution. With zinc foil (50 μm) as positive and negative electrodes and glass fiber as separator, 130 μL of the above electrolyte was added dropwise to assemble a Zn||Zn symmetrical battery and test its cycle performance at 20°C. Figure 5 It can be seen that a large number of zinc dendrites appear on the surface of the zinc electrode in Comparative Example 1. The aqueous zinc ion electrolyte prepared in Comparative Example 1 was used to assemble a Zn||Zn symmetrical battery, and a charge and discharge test was performed on a blue electric test system. Figure 2 As shown, the corrosion potential of the LSV curve of Comparative Example 1 is more negative and the corrosion current is larger, indicating that the corrosion resistance of the aqueous zinc ion battery electrolyte prepared in Comparative Example 1 to the zinc negative electrode is poor. Figure 3 As shown, at a current density of 0.2 mA cm -2 , the deposition capacity is 0.2 mAh cm -2 Under the test conditions, the battery cycle life is only 194h. Figure 4 As shown, at a current density of 2 mA cm -2 , the deposition capacity is 2 mAh cm -2 Under the test conditions, the Zn||Zn symmetrical battery short-circuited at around 130h. It may be that zinc dendrites were generated inside the battery, which pierced the diaphragm and caused the battery to short-circuit.
[0038] Example 2
[0039] The other conditions were the same as those in Example 1, except that malic acid was used as an additive.
[0040] Example 3
[0041] Other conditions were the same as those in Example 1, except that chloramphenicol was used as an additive.
[0042] Example 4
[0043] An aqueous zinc ion battery electrolyte and a preparation method thereof, comprising the following steps:
[0044] 1) Weigh 5.75 g zinc sulfate and mix with 10 mL deionized water and stir evenly to obtain 2 mol L -1 Zinc sulfate solution;
[0045] 2) Weigh 0.25 mg of folic acid additive and mix with the obtained 2 mol L -1 The zinc sulfate solution was ultrasonically mixed for 2 h and then stirred at a speed of 600 r / min for 6 h to prepare the electrolyte used.
[0046] Application of aqueous zinc ion battery electrolyte:
[0047] With zinc foil as positive and negative electrodes and glass fiber as separator, 130 μL of the above electrolyte was added to assemble a Zn||Zn symmetrical battery. The cycle life of the symmetrical battery was tested at 20°C, and its cycle performance was tested at 20°C. Figure 4 As shown, at a current density of 2 mA cm -2 , deposition capacity is 2 mA cm -2 Under the test conditions, the Zn||Zn symmetrical battery short-circuited at around 120h.
[0048] Example 5
[0049] An aqueous zinc ion battery electrolyte and a preparation method thereof, comprising the following steps:
[0050] 1) Weigh 5.75 g zinc sulfate and mix with 10 mL deionized water and stir evenly to obtain 2 mol L -1 Zinc sulfate solution;
[0051] 2) Weigh 0.5 mg of folic acid additive and mix with the obtained 2 mol L -1 The zinc sulfate solution was ultrasonically mixed for 2 h and then stirred at a speed of 600 r / min for 6 h to prepare the electrolyte used.
[0052] Application of aqueous zinc ion battery electrolyte:
[0053] With zinc foil as positive and negative electrodes and glass fiber as separator, 130 μL of the above electrolyte was added to assemble a Zn||Zn symmetrical battery. The cycle life of the symmetrical battery was tested at 20°C, and its cycle performance was tested at 20°C. Figure 4 As shown, at a current density of 2 mA cm -2 , the deposition capacity is 2 mAh cm -2 Under the test conditions, the Zn||Zn symmetrical battery short-circuited at around 160h.
[0054] Example 6
[0055] An aqueous zinc ion battery electrolyte and a preparation method and application thereof, comprising the following steps:
[0056] 1) Weigh 5.75 g zinc sulfate and mix with 10 mL deionized water and stir evenly to obtain 2 mol L -1 Zinc sulfate solution;
[0057] 2) Weigh 2 mg of folic acid additive and mix with the obtained 2 mol L -1 The zinc sulfate solution was ultrasonically mixed for 2 h and then stirred at a speed of 600 r / min for 6 h to prepare the electrolyte used.
[0058] Application of aqueous zinc ion battery electrolyte:
[0059] With zinc foil as positive and negative electrodes and glass fiber as separator, 130 μL of the above electrolyte was added to assemble a Zn||Zn symmetric battery, and the cycle life of the symmetric battery was tested at 20°C. Figure 4 As shown, at a current density of 2 mA cm -2 , the deposition capacity is 2 mAh cm -2 Under the test conditions, the Zn||Zn symmetrical battery short-circuited at around 140h.
[0060] Example 7
[0061] The other conditions were the same as those in Example 1, except that the prepared electrolyte was used to assemble a Cu||Zn asymmetric battery. Figure 6 As shown, at a current density of 1 mA cm -2 , the deposition capacity is 1 mAh cm -2 Under the test conditions, it has a long life of 936 cycles and a high Coulombic efficiency of 99.37%. Figure 7 As shown, at a current density of 8 mA cm -2 , the deposition capacity is 4 mAh cm -2 Under the test conditions, the addition of folic acid additive significantly improved the cycle life of aqueous zinc-ion batteries.
[0062] Comparative Example 2
[0063] The electrolyte is a 2 mol / L ZnSO4 aqueous solution, and the Cu||Zn asymmetric battery is assembled using the electrolyte. Figure 6 As shown, at a current density of 1 mA cm -2 , the deposition capacity is 1 mAh cm -2 Under the test conditions, it failed at the 81st cycle with an average Coulombic efficiency of only 99%, mainly due to the formation of dendrites and side reactions during the cycle.
[0064] Example 8
[0065] The other conditions were the same as those in Example 1, except that 2 mol / L zinc acetate solution was used instead of 2 mol / L zinc sulfate solution, and the prepared electrolyte was used to assemble a Cu||Zn asymmetric battery. -2 , the deposition capacity is 4 mAh cm -2 Tested under the test conditions, the test results are shown in Figure 7 .
[0066] Example 9
[0067] The other conditions were the same as those in Example 1, except that 2 mol / L zinc trifluoromethanesulfonate solution was used instead of 2 mol / L zinc sulfate solution, and the prepared electrolyte was used to assemble a Cu||Zn asymmetric battery. -2 , the deposition capacity is 4 mAh cm -2 Tested under the test conditions, the test results are shown in Figure 7 .
[0068] Example 10
[0069] The other conditions were the same as those in Example 1, except that 2 mol / L zinc chloride solution was used instead of 2 mol / L zinc sulfate solution, and the prepared electrolyte was used to assemble a Cu||Zn asymmetric battery. -2 , the deposition capacity is 4 mAh cm -2 Tested under the test conditions, the test results are shown in Figure 7 .
[0070] Embodiment 11
[0071] Other conditions were the same as those in Example 4, except that the Cu||Zn asymmetric battery was assembled, and the average coulombic efficiency was 97.71%.
[0072] Example 12
[0073] Other conditions were the same as those in Example 5, except that the Cu||Zn asymmetric battery was assembled, and the average coulombic efficiency was 97.25%.
[0074] Example 13
[0075] Other conditions were the same as those in Example 6, except that the Cu||Zn asymmetric battery was assembled, and the average coulombic efficiency was 99.04%.
[0076] Embodiment 14
[0077] Weigh 5.75 g of zinc sulfate and mix with 10 mL of deionized water and stir evenly to obtain 2 mol L-1 Zinc sulfate solution; weigh 2 mg of folic acid additive and mix with 2 mol L -1 The zinc sulfate solution was ultrasonically mixed for 2 h and then stirred at a speed of 600 r / min for 6 h to prepare the electrolyte used.
[0078] Application of aqueous zinc ion battery electrolyte:
[0079] With MnO2 as the positive electrode, zinc foil as the negative electrode, and glass fiber as the separator, 130 μL of the above electrolyte was added dropwise to assemble the battery. Figure 8 As shown in the graph, under the test condition of 5C, in about 900 cycles, the average Coulomb efficiency is maintained at 99.94% and the capacity retention rate is 77.1%. This shows that the addition of folic acid greatly improves the cycle stability and capacity of the full battery.
[0080] Comparative Example 3
[0081] A 2 mol / L ZnSO4 aqueous solution was prepared as the electrolyte, and a MnO2||Zn asymmetric cell (Coulomb efficiency 99.91%) was assembled.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that The aqueous zinc ion battery electrolyte contains a soluble zinc salt and an organic additive. The concentration of the soluble zinc salt in the electrolyte is 1 to 3 mol / L; the concentration of the organic additive in the electrolyte is 0.25 to 3 g / L.
2. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The organic additive is one or more of folic acid, malic acid and chloramphenicol.
3. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The soluble zinc salt is one or more of zinc borate, zinc chloride, zinc trifluoromethanesulfonate, zinc sulfate, zinc perchlorate and zinc acetate.
4. A method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The organic additive is added into the solution containing the zinc salt, and the mixture is uniformly mixed by ultrasonication.
5. The use of an aqueous zinc ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The aqueous zinc ion battery electrolyte is used in an aqueous zinc ion battery, wherein the aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm, and an electrolyte; the negative electrode is one of zinc sheet, zinc foil, zinc plate, and zinc powder material; The positive electrode is at least one of zinc metal, Prussian blue analogs, manganese-based oxides, vanadium-based oxides, and organic materials; The diaphragm is one of glass fiber, single-layer polypropylene film, single-layer polyethylene film, polypropylene + ceramic coating film, polyethylene + ceramic coating film, double-layer polypropylene / polyethylene film, double-layer polypropylene polypropylene and three-layer polypropylene / polyethylene / polypropylene film, Nafion membrane, PVDF membrane, polyester membrane, cellulose membrane, polyimide membrane, non-woven fabric diaphragm, and inorganic composite membrane.
6. The use of an aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The Prussian blue analogue is one of HCF, ZnHCF and CuHCF.
7. The use of an aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The manganese-based oxide is one of MnO2, Mn2O3, Mn3O4, ZnMn2O4, and MgMn2O4.
8. The use of an aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The vanadium-based oxides are V2O5, VO2, V2O3, V6O 13 , one of vanadates NaV3O8·1.5H2O, LiV3O8, and CuV2O6.
9. The use of an aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The organic material is polyaniline or quinone compound.
Citation Information
Cited By
Polyethylene glycol diacrylate aqueous zinc ion battery electrolyte and preparation and application thereof
CN121584052A